Identification of Antibiotic-Producing Bacteria from Extreme Microhabitat in Molecular Mangrove Ecosystems and Their Activity on Pathogenic Bacteria (Vibrio alginolyticus) - Desy Mutia Sari; Irwan Effendi; Nursyirwani Nursyirwani (Jurnal Perikanan dan Kelautan, 2019)
The presence of antibiotic-producing bacteria from microhabitat in mangrove ecosystems can be useful to produce new antibiotics for industrial and environmental conservation. Mangrove ecosystems in Dumai have the potential to possess antibiotic-producing bacteria that have not been much studied. The objective of this research was to obtain antibiotic-producing bacteria from extreme microhabitats in the mangrove ecosystem in suppressing the growth of pathogenic bacterial pathogens (Vibrio alginolyticus). Samples were taken from several microhabitat mangrove areas in Dumai (Kelurahan Purnama Dumai), Riau Province. The survey method is used for identification, antibacterial test against pathogenic bacteria (V. alginolyticus). Bacterial isolation was carried out using the pour plate method and purification was carried out using the quadrant streak method. Identification is carried out through observations of macroscopic, microscopic morphology, biochemical tests, antagonism tests (agar diffusion method on agar nutrient media) and DNA analysis. Sequencing of 16S rDNA from the best antibiotic-producing bacterial isolates indicated that molecularly identified of Bacillus amyloliquefaciens, Bacillus cereus, Enterobacter hormaechei, Klebsiella pneumonia, and Enterococcus gallinarum. All bacteria were able to inhibit the growth of V. alginolyticus